The Effect of Low Ambient Relative Humidity on Physical Performance and Perceptual Responses during Load Carriage - Mekjavic, Igor B.; Ciuha, Ursa; Grönkvist, Mikael; Eiken, Ola (Frontiers in Physiology, 2017)
Introduction: The study evaluated the effect of low ambient relative humidity on physical performance and perceptual responses during load carriage in a hot environment. Methods: Ten heat-unacclimatised male subjects participated in three 130-min trials, during which they walked on a treadmill, carrying a load of 35 kg, at a speed of 3.2 km.h-1, with an incident wind at the same velocity and ambient temperature at 45°C. Each trial commenced with a 10-min baseline at 20°C and 50% relative humidity (RH), the subjects transferred to a climatic chamber and commenced their simulated hike, comprising two 50-min walks separated by a 20-min rest period. In two, full protective equipment (FP) trials, RH was 10% (partial pressure of water vapour, pH2O=7.2 mmHg) in one (FP10), and 20% (pH2O=14.4mmHg; FP20) in the other. In the control trial, subjects were semi-nude (SN) and carried the equipment in their backpacks; RH was 20%. Measurements included oxygen uptake, ventilation, heart rate, rectal and skin temperatures, heat flux, temperature perception, and thermal comfort. Results: In FP20, 4 subjects terminated the trial prematurely due to signs of heat exhaustion; there were no such signs in FP10 or SN. Upon completion of the trials, pulmonary ventilation, heart rate and rectal temperature were lower in FP10 (33±5 l/min; 128±21 bpm; 38.2±0.4°C) and SN (34±4 l/min; 113±18 bpm; 38.1±0.4°C than in FP20 (39±8 l/min; 145±12 bpm; 38.6±0.4°C). Evaporation was significantly greater in the SN compared to FP10 and FP20 trials. FP10 was rated thermally more comfortable than FP20. Conclusion: A lower ambient partial pressure of water vapour, reflected in a lower ambient relative humidity, improved cardiorespiratory, thermoregulatory and perceptual responses during load carriage.